On human remains: Values and practice in the home archiving of cherished objects - Kirk, David; Sellen, Abigail (Transactions on Computer-Human Interaction, 2010)
Creating digital archives of personal and family artifacts is an area of growing interest, but which seemingly is often not supported by a thorough understanding of current home archiving practice. In this article we seek to excavate the home archive, exploring those things that people choose to keep rather than simply accumulate. Based on extensive field research in family homes we present an investigation of the kinds of sentimental objects, both physical and digital, to be found in homes, and through in-depth interviews with family members we explore the values behind archiving practices, explaining why and how sentimental artefacts are kept. In doing this we wish to highlight the polysemous nature of things and to argue that archiving practice in the home is not solely concerned with the invocation of memory. In support of this we show how sentimental artifacts are also used to connect with others, to define the self and the family, to fulfill obligations and, quite conversely to efforts of remembering, to safely forget. Such values are fundamental to family life where archiving takes place and consequently we explore how home archiving is achieved as a familial practice in the negotiated spaces of the home. From this grounded understanding of existing practices and values, in context, we derive requirements and implications for the design of future forms of domestic archiving technology.